Environmentally Friendly Livestock Waste Management in High-Population Areas in Karang Ploso Malang Regency East Java - Muhammad Arwani; Abdul Hakim; Agus Budiarto; Gatot Ciptadi; Yudit Oktanella (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This abstract explores the need for integrated development in the agricultural and livestock sectors of Ngenep Village, Karangploso, Malang Regency, focusing on utilizing livestock waste effectively. Method: The study details the steps to develop a system for producing organic fertilizer and animal feed from agricultural and livestock waste. It highlights the successful implementation within the "Langgeng Mulya" dairy cattle farming community, emphasizing the utilization of waste for organic fertilizer in chili and tomato cultivation. Practical Applications: The research findings showcase the positive response of local farmers to the utilization of livestock waste, addressing the scarcity of organic fertilizer, particularly for tomato and chili growers. This sustainable approach fosters self-sufficiency and offers insights into waste-to-resource strategies. Conclusion: This study underscores the importance of integrating the agricultural and livestock sectors for sustainable waste management and resource utilization. It provides valuable lessons for enhancing the efficiency of rural development programs.